Analisa kecurangan laporan keuangan dengan perspektif teori Fraud Hexagon - Preicilia, Claudia; Wahyudi, Ickhsanto; Preicilia, Anita (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of this study was to determine whether financial stability, whistleblowing system, audit opinion, director turnover, CEO education, and CEO duality had an effect on the occurrence of fraudulent financial reporting. The method uses a research design that is causal-comparative. The sampling technique used purposive sampling with a sample of 62 secondary data in the form of annual financial reports and other financial data. The results of research and descriptive statistical tests using the Beneish M-Score show that financial stability, violation reporting system, audit opinion, director turnover, CEO education, and CEO duality simultaneously have a significant effect on the prediction of fraudulent financial reporting. Partially from the independent variable test, the results show that the variable of director turnover and CEO education has a significant effect on the prediction of fraudulent financial reporting with a p-value of Sig 0.002 for director turnover and a p-value of Sig 0.042 for CEO education with a probability value of less than Sig. 0.05. While other research variables, namely financial stability, whistleblowing system, audit opinion, and CEO duality have no effect on the prediction of fraudulent financial reporting or the Sig value is greater than 0.05.